DENTAL MANAGEMENT OF THE CARDIAC PATIENTS - Alina Saghin; Aurel Lazăr; Liviu Lazăr; Marius Rus (Romanian Society of Oral Rehabilitation, 2014)
Recent epidemiological studies reveal that oral pathogens are co-factors in the formation of atheroma plaques and the advanced periodontitis represents a risk factor for cardiovascular diseases. The pathogenic bacterial burden reprents the essential in the association of coronary artery disease with periodontitis, which is extremely relevant to the periodontal lesions that develop in the oral cavity, a space crossed by the most unexpected bacterial combinations from alimentation and air. The main objective of the study is to determine the prevalence of bacterial burden in cardiac patients with periodontal disease and to follow up the effects of dental procedures associated with low-doses of antibiotics in relation with coronary atherosclerotic disease. The study implies a lot of 92 patients undergoing the following investigations: 1. Panoramic radiography of the oral cavity, 2. Clinical examination of the oral cavity, 3. Bacterial examination on the dental plaque's level 4. identification of the presence of serum inflammatory markers, 5. Bio-humoral examinations, 6. Cardiology specialty examination. The control of periodontal infection could lead to the improvement in the levels of systemic inflammation markers and in those of endothelial dysfunction's markers. As far as the control of periodontal infection decreases the incidence of coronary atherosclerotic cardiovascular events can be assumed that the dental management of cardiovascular disease is in progress.